1979
DOI: 10.1093/nar/6.6.2327
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR investigation of the conformational states of DNA in nucleosome core particles

Abstract: In this study 1H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…This possibility is unlikely because integrated intensities correspond to at least 80% of the expected intensity, based on the spectral range (11-15 ppm) examined, the breadth of the lines observed, and the integrated intensities observed with lower molecular weight samples. Furthermore, the spectra of 140-bp DNA from nucleosome core particles fit well with the series of DNA lengths presented here (24).…”
supporting
confidence: 74%
“…This possibility is unlikely because integrated intensities correspond to at least 80% of the expected intensity, based on the spectral range (11-15 ppm) examined, the breadth of the lines observed, and the integrated intensities observed with lower molecular weight samples. Furthermore, the spectra of 140-bp DNA from nucleosome core particles fit well with the series of DNA lengths presented here (24).…”
supporting
confidence: 74%
“…This is an ideal situation since it is much shorter than the spin-lattice relaxation time and the time limit at which spin diffusion should set in. A typical mixing time for a biomolecule of comparable size, say, for instance, a small oligonucleotide 10-mer duplex, is 350 ms (Feignon et al, 1979(Feignon et al, , 1983. The NOE spectrum at 200 ms mixing time ( Figure 5) contained cross peaks corresponding to interactions between H-1 of the distal glucosamine residue and H-4, H-6R, and H-6S of the proximal residue.…”
Section: Resultsmentioning
confidence: 99%
“…While spectral studies agree that the conformation of nucleosome DNA is of the "B-genus" (23)(24)(25)(26), there has been considerable discussion of the way in which this DNA may be deformed to permit superhelix formation.…”
Section: Conformation Of the Dnamentioning
confidence: 99%
“…Although it has been suggested that abrupt bends or kinks in the DNA might occur at periodic intervals (27,28), no special class of backbone conformations has been detected by either phosphorus or proton magnetic resonance (25,26,(29)(30)(31). Moreover, one can build continuously deformed duplex structures that violate none of the known restrictions on bond angles or interatomic contacts in polynucleotides (22,32).…”
Section: Conformation Of the Dnamentioning
confidence: 99%